2021
DOI: 10.3390/cimb43020035
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Pharmacological Studies on the Antioxidant, Thrombolytic, Anti-Inflammatory, and Analgesic Activity of Molineria capitulata

Abstract: Molineria capitulata is an ornamental plant that has traditionally been used to treat several chronic diseases. The present study was designed to examine the antioxidant, cytotoxic, thrombolytic, anti-inflammatory, and analgesic activities of a methanolic extract of M. capitulata leaves (MEMC) using both experimental and computational models. Previously established protocols were used to perform qualitative and quantitative phytochemical screening in MEMC. A computational study, including molecular docking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Green Tea Polyphenols are involved in immunoregulation and have antibacterial, antioxidant and anti-inflammatory activities, and it is used against diseases caused by the coronavirus [ 23 ]. The methanol extracts of Molineria capitulata have antioxidization, cytotoxicity, thrombolysis, anti-inflammation, and analgesic properties [ 24 ]. Last but not least, cannabinoids can be used as a source of new functional food ingredients and nutraceuticals, which are effective in treating and preventing gastrointestinal diseases [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Green Tea Polyphenols are involved in immunoregulation and have antibacterial, antioxidant and anti-inflammatory activities, and it is used against diseases caused by the coronavirus [ 23 ]. The methanol extracts of Molineria capitulata have antioxidization, cytotoxicity, thrombolysis, anti-inflammation, and analgesic properties [ 24 ]. Last but not least, cannabinoids can be used as a source of new functional food ingredients and nutraceuticals, which are effective in treating and preventing gastrointestinal diseases [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids present in extracts, and fractions might be responsible for the thrombolytic activity observed in this study [ 22 ]. Also, alkaloids, tannins, and saponins, which were identified in the plant in previous studies [ 28 – 31 ], are involved in thrombolytic activities [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary polyphenols may also suppress the growth of adipose tissue through their antiangiogenic activity and by modulating adipocyte metabolism [ 21 ], as well as thrombolytic activity by dissolving blood clots [ 22 ]. Moreover, alkaloids, tannins, and saponins are involved in thrombolytic activity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pharmacological studies have shown that some medicinal plants are safe natural analgesics and have potential therapeutic advantages. For example, Molineria capitulata and Spirulina platensis have anti-inflammatory, antioxidant, and analgesic effects [ 15 , 16 ]. Bromelain is a natural drug to alleviate the symptoms of arthritis (including joint pain and stiffness) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%